132k views
1 vote
If f(x) = x-1 and g(x) =2x-3 find the sum, difference, product and quotient of these two functions

1 Answer

3 votes
We have the following functions:
f (x) = x-1
g (x) = 2x-3

For the sum we have:
f (x) + g (x) = (x-1) + (2x-3)
f (x) + g (x) = 3x - 4

For subtraction we have:
f (x) - g (x) = (x-1) - (2x-3)
f (x) - g (x) = -x + 2

For the product we have:
f (x) * g (x) = (x-1) * (2x-3)
f (x) * g (x) = 2x ^ 2 - 3x - 2x + 3
f (x) * g (x) = 2x ^ 2 - 5x + 3

For the quotient we have:
f (x) / g (x) = (x-1) / (2x-3)
User Nathan Friedly
by
4.9k points